Alkyl Monolayers on Silica Surfaces Prepared from Neat, Heated ClSi(CH₃)₂(CH₂)₁₇CH₃ Analyzed by XPS - Husseini, Ghaleb (2002)
Silane monolayers on silica, prepared from mono-, di- and trichlorosilanes, are widely used in industry for surface functionalization and modification. However, unlike di- and trichlorosilanes, monochlorosilanes are particularly easy to work with because they can dimerize, but not polymerize, upon reaction with water. Typically, an organic solvent is used when depositing a silane monolayer. Here we show XPS spectra of monolayers of ClSi(CH₃)₂(CH₂)₁₇CH₃ (octadecyldimethylchlorosilane, CAS# 18643-08-8) on silicon oxide (silicon wafer) prepared using a rapid, solvent-free approach. Reaction conditions are 120 °C for 10 min using the neat (pure) compound, and no inert atmosphere or special treatment of the compound is required.